Biodegradable polymer versus second‐generation durable polymer drug‐eluting stents in patients with coronary artery disease: A meta‐analysis. Issue 11 (5th October 2018) - Wu, James J.; Way, Joshua A.H.; Roy, Probal; Yong, Andy; Lowe, Harry; Kritharides, Leonard; Brieger, David
Abstract: Aims: Biodegradable polymer drug‐eluting stents (BP‐DES) were developed in hopes of reducing the risk of stent thrombosis. The comparison of this new stent platform with second‐generation durable polymer drug‐eluting stents (DP‐DES) has not been well described. We, therefore, performed a meta‐analysis to evaluate the safety and efficacy profiles of BP‐DES versus second‐generation DP‐DES in patients with coronary artery disease. Methods and Results: Electronic database searches were conducted, from their dates of inception to June 2018, to identify randomized controlled trials (RCTs) comparing patients with either BP‐DES or second‐generation DP‐DES. Risk estimates were expressed as risk ratios (RRs) with 95% confidence intervals (CIs). We also performed a landmark analysis beyond 1 year and sensitivity analyses based on different variables. A total of 24, 406 patients from 19 RCTs were included in the present meta‐analysis. There were no significant differences between BP‐DES and second‐generation DP‐DES for the risks of definite or probable stent thrombosis (RR 0.88; 95% CI, 0.69–1.12; P = 0.29), myocardial infarction (RR 0.97; 95% CI, 0.86–1.09; P = 0.59), cardiac death (RR 1.08; 95% CI, 0.92–1.28; P = 0.34), all‐cause death (RR 1.02; 95% CI, 0.91–1.13; P = 0.77), target lesion revascularization (RR 1.05; 95% CI, 0.94–1.17; P = 0.38), and target vessel revascularization (RR 1.05; 95% CI, 0.95–1.16; P = 0.36). Similar outcomes were observed regardless of anti‐proliferative drug and duration of dual antiplatelet therapy (all P > 0.05). Conclusion: Our findings demonstrate similar safety and efficacy profiles between BP‐DES and second‐generation BP‐DES, with comparable rates of stent thrombosis.